2023
DOI: 10.1186/s13023-023-02782-7
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical microvascular changes in ANCA-vasculitides: the role of optical coherence tomography angiography and nailfold capillaroscopy in the detection of disease-related damage

Abstract: Background Both cardiovascular and complement-mediated disorders might lead to microvascular damages in anti-neutrophil cytoplasm autoantibodies (ANCA)-associated vasculitides (AAV). We aimed at investigating, for the first time, subclinical microvascular abnormalities with non-invasive techniques in AAV patients by analyzing both retinal and nailfold capillary changes. Retinal plexi were investigated using optical coherence tomography angiography (OCT-A), while nailfold capillary changes by vi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Considering the emerging role of these biomarkers in SLE pathogenesis, it deserves further research in exploring the correlation between retinal changes and these biomarkers from the blood samples. Additionally, it has been reported that there were correlations between nailfold capillaroscopy and VD of OCTA in several immune disorders, such as systemic sclerosis, psoriatic arthritis, and ANCA-vasculitides ( 39 41 ). Encouragingly, the combined examination results of ocular microvascular alterations and fingertip perfusion may complement traditional diagnostic methods of these disorders ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the emerging role of these biomarkers in SLE pathogenesis, it deserves further research in exploring the correlation between retinal changes and these biomarkers from the blood samples. Additionally, it has been reported that there were correlations between nailfold capillaroscopy and VD of OCTA in several immune disorders, such as systemic sclerosis, psoriatic arthritis, and ANCA-vasculitides ( 39 41 ). Encouragingly, the combined examination results of ocular microvascular alterations and fingertip perfusion may complement traditional diagnostic methods of these disorders ( 39 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the use of non-invasive techniques such as OCT and OCT angiography in patients with rheumatological conditions may serve as an additional tool for their followup. Indeed, the current literature contains several examples of clinical studies of this nature involving patients with rheumatoid arthritis [39-41], Sjogren's syndrome [42][43][44], ANCA-vasculitis [45] and systemic lupus erythematosus [46,47], highlighting once more the significance of a multidisciplinary approach.…”
Section: Discussionmentioning
confidence: 99%
“…Triggianese et al [15] Observational study was realised on 23 patients affected by AAV. They were analysed via NVC.…”
Section: Capillaroscopic Strategy and Methods Capillaroscopy Findingsmentioning
confidence: 99%
“…Recently, there has been increased attention on the utility of the non-invasive microvascular inspection of the nailfold bed for several systemic diseases [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Precisely, nail bed capillaroscopy is useful for assessing subjects for potential scleroderma and other autoimmune diseases [26].…”
Section: Nailfold Video Capillaroscopymentioning
confidence: 99%
See 1 more Smart Citation